THE INFLUENCE FACTORS OF ELECTRONIC WORD OF MOUTH BEHAVIOUR IN FACULTY OF NURSING GARUT CLASS PADJADJARAN UNIVERSITY - Novita Kamaruddin; Megawati Simanjuntak; Lilik Noor Yuliati (Universitas Padjadjaran, 2021)
Higher education in increasing competition needs to provide excellent quality services for students to college. Students satisfaction will be encouraged to disseminate their campus information through electronic word of mouth (eWOM). EWOM is a form of consumer willingness to voluntarily provide recommendations for others to buy or use products from companies through the internet. This research was conducted to analyze the quality of service, promotion, brand image and motivation towards eWOM. The research was quantitative research using a descriptive approach. The data were analyzed using SEM Lisrel (Structural Equation Modeling). This study was conducted of student from Faculty of Nursing Garut class who actively carry out lecture with total sample of 309. The findings of this research showed that there was a significant relationship between service quality on brand image, there is a meaningful relationship between the promotion of brand image, there is no significant relationship between service quality on eWOM, brand image has a significant to eWOM and motivation has a significant relationship to eWOM.